DNA linked gold nano particle satellite structure synthesis and its application in potassium ion sensing - Chiang, Justina Wei Ching (2015)
Potassium ions are important in the human body as they help in the synthesis of protein and aid in the function of different physiological function of the body. A lack of potassium ions would result in a fatigue, abnormal heart beat and so on. As compared to other ions, potassium ions found in very low concentration in the body. Hence, there is a need to develop a biosensor that is sensitive to minute concentration of potassium ions. The detection of potassium ions through the conformational change of aptamer from loose ends to G-quadruplex has proven to be able to detect micrometer and nanometer concentration of potassium ions. In recent years, there has been an increase in the use of nanomaterials for making biosensor. Among the nanomaterials, gold nanoparticles have received the most interest. Its ability to quench fluorophore more efficiently, the localized surface plasmon resonance (LSPR) and its ability to detect at nano-level makes it useful as fluorescence probe as a biosensor. In this project, gold nanoparticle functionalized with oligonucleotides linked with fluorescein will be synthesis. In the presence of potassium ion, the oligonucleotide will change its conformation to form G-quadruplex which resulted in the quenching of fluorescein by gold nanoparticle. The quenching of fluorescein (FAM) is detected by the decrease in fluorescein intensity by UV spectrometry. The sensitivity of the oligonucleotides used in this experiment could not be determined as few experiments were done and other factors might have interfered with the sensing of potassium ions.